Beija-flores e seus recursos florais no Parque Nacional da Serra da Canastra - Silva, Monique Maianne da (2021)
Hummingbirds make up the phenotypically most specialized group in floral visitation. Indeed, many species of plants throughout the Americas depend on these birds to complete their reproductive cycle. Despite the inestimable contribution of existing studies on these relationships to the knowledge of mutualistic interactions, some ecosystems, such as the rupestrian fields sensu lato, are little explored in this context. Thus, the present work aimed to characterize the interactions between hummingbirds and plants in two phytophysiognomies of this ecosystem, rupestrian fields sensu stricto and forest islands represented by riparian forests, immersed in the Cerrado domain. We carried out field collections for one year in the Serra da Canastra National Park, one of the largest remnants of the Cerrado domain and well represented by ecosystems of rupestrian fields. Through observations on transects distributed in the two selected phytophysiognomies, we aim to characterize the interactions between hummingbirds and plants in terms of their general patterns (chapter 1) and in the light of the ecological networks approach (chapter 2). Specifically, in the first chapter, we investigated variations in the richness of plants visited by hummingbirds, hummingbird richness and abundance, total floral visitation and agonistic behavior of hummingbirds between two annual seasons (rainy and dry), syndromes pollination and phytophysiognomies. In the second chapter, we seek to assess variations in the patterns of interactions between the two habitats sampled in the light of the ecological network approach.